Highly efficient & economic synthesis of CoS1.097/nitrogen-doped carbon for enhanced triiodide reduction. (15th April 2021) - Chang, Jiangwei; Huang, Longlong; Yu, Chang; Ding, Yiwang; Yao, Chun; Qiu, Jieshan
Abstract: The rational design and feasible synthesis of the metal organic frameworks (MOFs)-derived carbon-based materials with excellent triiodide reduction (IRR) performance still remains challenging. Generally, for the present synthesis methods, the MOFs-derived bulk or big-sized metallic particles imbedded into the carbon matrix are directly removed and discarded without considering to be further utilized, which can not meet the requirements of green chemical engineering techniques. Herein, we report a green & atomic economic synthesis route for the in situ utilization and conversion of these metallic source to highly active CoS1.097 species constructed on the nitrogen-doped carbon (denoted as CoS1.097 /ZNCA) by using zeolitic imidazolate framework (ZIF-67) as the precursor. Notably, the CoS1.097 /ZNCA CE exhibits an excellent power conversion efficiency of 8.54%, surpassing that of the noble Pt CE. This significantly improved electrocatalytic activity towards the IRR is contributed to the synergistic effects between the highly electroactive CoS1.097 species and the carbon framework acting as the conductive substrate. Graphical abstract: We have reported a green and atomic economic route to the CoS1.097 /ZNCA functional materials by adopting ZIF-67 as the precursor. As an example of IRR, the CoS1.097 /ZNCA CE demonstrates a remarkably superior power conversion efficiency of 8.54% and a better stability in sharp comparison with that of Pt CE. Image 1